Referential and sectorial criteria on relative decision making in dealing with childhood and adolesence in the local public area. - Alarcón Espinoza, Marina; Rehbein Felmer, Lucio (Última Década, 2020)
The present investigation had by objective to characterize decision making of those who have the possibility of bearing on people under the age of 18 years, in the commune of Temuco. Previously, as much as considering the criteria to the base of the decision as the perspective of future wished for childhood and adolescence. The study was of descriptive character, in a qualitative frame of methodology, in which a design of multiple cases in three stages was used: i) survey, ii) Delphi group, and iii) diagnosis-propositivo workshop. In each stage the information of the sectors was compiled separately, education, health, justice and government. The results, show four operative criteria in decision making, and two prospective, associated to the future vision that the responsible agents consider in their decisional process. These results are discussed, taking in consideration the present cultural and institutional dynamics, and the necessity of an active participation on the part of children and adolescents, in the development of their localities and regions.